Mechanisms Involved in the Stimulatory and Inhibitory Effects of 5-Hydroxytryptamine on Vagal Mechanosensitive Afferents in Rat Lung - Lin, You Shuei; Hsu, Chun-Chun; Ruan, Ting; Lee, Lu-Yuan (Frontiers in Physiology, 2022)
Mechanosensitive vagal afferents in the lung, rapidly and slowly adapting receptors (RARs and SARs, respectively), play an important role in eliciting the reflexes that regulate the normal airway function. A profound bronchoconstrictive effect of 5-HT has been extensively reported in various animal species, but its influence on the SAR and RAR activity is not known. This study investigated the effect of 5-HT on these receptors, and the possible mechanisms involved. Single-fiber activities of these afferents were measured in anesthetized, open-chest, and mechanically ventilated rats. Our results showed that intravenous injection of 5-HT evoked a consistent and pronounced stimulation of phasic RARs. In contrast, 5-HT generated an inconsistent and paradoxical action on SARs: no effect in 29% (5 of 17) of the SARs; stimulation in 35% (6 of 17); and inhibition in the remainder. These responses of both RARs and SARs to 5-HT were reproducible and dose-dependent. After the injection of a high dose of 5-HT (16 µg/kg), the receptor responses slowly reached a peak (after ~8 s) and returned toward the baseline in ~20 s, accompanied by a consistent increase in total pulmonary resistance and a decrease in dynamic lung compliance in a temporal pattern very similar to the increased receptor activity. When these changes in lung mechanics induced by 5-HT were prevented by pretreatment with salbutamol, a β2 adrenergic receptor agonist, the delayed responses of both RARs and SARs to 5-HT were also abolished, except that the immediate stimulatory effect on a subset of RARs, the silent RARs, was not affected. In conclusion, 5-HT generated a delayed stimulatory effect on RARs and a paradoxical effect on SARs, which resulted primarily from the 5-HT-induced changes in mechanical properties of the lung.